O estudo das novas legislações de estágio e o contexto no curso de serviço social da FCHS - UNESP- Campus de Franca - Pequiá, Raquel Renzo da Silva [UNESP] (2015)
This study aims to reflect on the stage as a privileged space for learning, a good time for the trainee to develop their professional identity matrix, carried out by responsibility and commitment and, to the extent that the student is inserted in this educational activity, stage is effectively the professional legitimacy of space. Thus, the present work aims to hold a debate on that legislation and the context in the course of Social Work, Faculty of Humanities and Social Sciences - UNESP - Franca. The study sought to analyze the understanding of teachers involved with the theme, given the impact of new legislative and regulatory changes applicable: Course coordinators of Social Work, internship sector coordinators and supervisors of the training group. To better grasp the stage setup supervised the course of UNESP, we conducted mapping of training camps supervised from 2009 to 2014. We assume that the supervised training, according to the curriculum guidelines of Social Work, is a must-curricular activity, which is established from the insertion of the student in social and occupational space and aims his training for professional practice. This research points to the need to understand and question the supervised training in higher education, linked to educational principles by identifying the current configuration of supervised training in social work from the perspective of new legislation and regulations in force until the year 2014